The Effect of Using Kahoot Application To Teach Grammar Eighth Grade Students in Junior High School - M Hasymi Hamdani; Dian Novita (Indonesian Journal of Cultural and Community Development, 2021)
Grammar is the most important aspect to be studied and explored, because using the correct grammar will form and build a correct sentence. In the Industrial Revolution 4.0 era, which affects the education system by using technology, one of which is by using the Kahoot application in the learning process. The research population includes eighth grade students, consisting of 18 students at SMP Muhammadiyah 9 Boarding School Tanggulangin in the academic year of 2020/2021. This study uses a pre-experiment that uses one class. the average value between the pre-test and post-test experienced a difference. the average value of the pre test is 46.66 and the average value of the post test is 76.94. The significant value of the research was 0.000 < significant level 0.05, meaning that there is an effect of Kahoot application for teaching grammar of the eighth grade students at SMP Muhammadiyah 9 Boarding School Tanggulangin.